Loan spreads and credit cycles: The role of lenders' personal economic experiences - CARVALHO, Daniel (Institutional Knowledge at Singapore Management University, 2023)
We provide evidence that changes in lender optimism can lead to excessive fluctuations in credit spreads across the credit cycle. Using data on the real estate properties of loan officers originating large corporate loans, we find that credit spreads overreact to sophisticated lenders' recent local economic experiences, captured by local housing price growth. These effects are only present when borrowers own real estate assets and during times of greater uncertainty about real estate values, i.e., boom-and-bust cycles in housing prices. Our analysis suggests that recent personal experiences shape sophisticated lenders' beliefs about real estate values, which affect their pricing decisions.